PERAN FORUM KOMUNIKASI ANAK KOTA BANDUNG MELALUI PROGRAM PANGLIMA DALAM MEMBANGUN KESADARAN ANTI-BULLYING (Studi Kasus Sekolah Dasar Swasta As-Salam) - Hilda Fadilah; Diah Gusrayani; Dety Amalia Karlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the socialization strategies carried out by the Forum Komunikasi Anak Kota Bandung (FOKAB) through the PANGLIMA program as an effort to prevent bullying in elementary schools. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. The research informants consisted of FOKAB administrators and facilitators, teachers at SDS As-Salam, and elementary school students. The findings show that the PANGLIMA socialization strategy was designed in a creative and contextual manner through role-playing methods, the use of visual media, and the symbolic approach of "7M", which helps children understand practical actions to take when facing bullying. This strategy proved effective in increasing students’ awareness of the forms and impact of bullying, as well as in fostering empathy and the courage to take action. Although the program was well implemented, obstacles were found in the form of limited follow-up from external parties and suboptimal coordination between the school and FOKAB after the activity. Therefore, program sustainability and synergy among all stakeholders are needed to create a truly safe and child-friendly school environment.